(untitled) (De la Crítica, 2023)
This study aimed to transform the teaching of reading in instrumental English teachers in Health Science Area at UNEFM, Miranda Municipality of Falcon State. This study is a qualitative approach based on participatory action research, which arose from a diagnosis made by the researcher who after interacting with the social actors, detected that teachers needed to improve limitations presented in relation to the teaching and assessment reading. This allowed planning; acting, observing and reflecting on the reality to then plan and carry out a training program considering the meaningful teaching model as a strategy for transforming action. The results were positive because teachers not only got new knowledge but also participated actively, exchanged their experiences and reflected on their limitations. Therefore, it can be established that it allowed teachers to reflect and elicit an effective communication of the knowledge they wish to facilitate.